MEDIA AUDIO VISUAL : PENGARUHNYA TERHADAP PERKEMBANGAN MORAL ANAK USIA DINI - Hasibuan, Rabitah Hanum; ., Veryawan; Tursina, Ade (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The purpose of this study was to determine children's moral development, the implementation of audio-visual media and to determine the effect of audio-visual media on children's morale in RA Hj. Fauziah, Binjai Timur District, Binjai City. The research conducted is quantitative in nature. In quantitative research, generally the data obtained is in the form of numbers or scores that are combined after taking the score through a questionnaire distributed to the research sample. Henceforth, these numbers are tested with numbers that become the second variable so that there will be a final number or score that can determine whether there is a relationship between the two variables that influence each other or not. The type of statistic used is the Product Moment Person Correlation statistic, which is to determine the effect of audio-visual media on children's morale in group B at RA Hj. Fauziah, Binjai Timur District, Binjai City. The population in this study were RA Hj students. Fauziah, Binjai Timur District, Binjai City in the 2020/2021 school year, totaling 63 people consisting of 38 male students and 25 female students. The results of the research using audio visual media can be said to be good. This can be proven by the value obtained, namely P = 72.93%. Research on children's morale can be said to be very good. This can be proven by the value obtained, namely P = 80.38%. There is a significant influence between the audio-visual media on children's morals as evidenced by the value of the correlation coefficient (r) which shows the level of correlation between variable X (audio-visual media) and variable Y (children's moral in group B) of r = 0.68 with a level of correlation high. Based on the t statistical test, namely t count = râˆš (n-1) the result is 3.18. So, it can be concluded that there is a significant influence between audio-visual media on children's morale in group B in RA Hj. Fauziah Binjai.